Chemistry Game Cards as an Alternative Media for Learning: A Literature Review - Nadila, Nadila; Enawaty, Eny; Erlina, Erlina; Masriani, Masriani (Universitas Pendidikan Mandalika, 2024)
Along with many chemical game media studies in the last 5 years, therefore the purpose of this literature review is to provide the latest information regarding student perspectives on chemical game card media. The review was conducted by searching international articles from ScienceDirect, Pubmed, Mendeley Search, ERIC, ACS Publication and Springer Link databases related to articles published between January 2019 and September 2024. To ensure conclusions based on high-quality evidence with longitudinal studies with a sample of >500 articles within the last 5 years, the search resulted in 6,779 articles from 6 databases. With a total of 23 articles with student subjects and 18 articles with student subjects who expressed their opinions about chemistry games and 2 articles with review article subjects. Overall, students and university students stated that chemistry game activities are effective as an alternative fun learning media to increase student engagement, motivation and learning outcomes. However, in this review, it was found that the use of games integrated with the internet was less in secondary schools than in universities. Meanwhile, the use of chemistry games without internet integration in high school and college is relatively the same. Overall, the perspectives of students and college students showed a positive attitude towards chemistry games.